The influence of geometrical shapes of stenosis on the blood flow in stenosed artery - Sarfaraz Kamangar,; Irfan Anjum Badruddin,; Ahamad, N. Ameer; Kalimuthu Govindaraju,; N. Nik-Ghazali,; Ahmed, N.J. Salman; A. Badarudin,; Khan, T.M. Yunus (Penerbit Universiti Kebangsaan Malaysia, 2017)
The present work was carried out to investigate the blood flow behavior and the severity of blockage caused in the arterial passage due to the different geometries such as elliptical, trapezium and triangular shapes of stenosis. The study was conducted with respect to various sizes of stenosis in terms of 70%, 80% and 90% area blockage of the arterial blood flow. The study was carried out numerically with the help of advance computational fluid dynamic software. It was found that the shape of the stenosis plays an important role in overall pressure drop across the blockage region of artery. The highest level of pressure drop was observed for trapezoidal shape of stenosis followed by elliptical and then by triangular shaped stenosis. The wall shear stress across the stenosis is great for trapezoidal shape followed by triangular and elliptical stenosis for same blockage area in the artery.